Religious Moderation Virtual Activities on Millenials during the COVID-19 Pandemic - Siti Munawati; Nur Halimah (AL-ISHLAH: Jurnal Pendidikan, 2022)
Mosques as national character builders cannot be separated from changes, namely moderation, which must be understood as a shared commitment to maintain balance in the environment that can have a major impact on society. Religion is entering the sphere of political life, economy, education, industry, globalization, pandemics, the environment and so on. The purpose of this study is to examine millennial religious moderation in mosque-based development through virtual activities at the Istiqlal mosque in Jakarta according to the perspective of Islamic education. The method used in this research is Field research in the form of documentation, interviews and observations with case studies about the method of da'wah programs with virtual activities with the approach model used in running the program during this Covid-19 Pandemic. So that virtual da'wah activities for the millennial generation can run and function to fill the void that is felt internally and publicly at the Istiqlal mosque in accessing religious knowledge so that in the digital era, the millennial generation is very easy to ask questions virtually, both on the website and on social media platforms. This virtual activity carried out at the Istiqlal mosque specifically for the study of the Youth Taklim assembly, called the millennial generation, contains various multimedia components, as an ideal medium for delivering material digitally. Then it was introduced to millennials and diaspora by utilizing digital promotions. The vision is for the Istiqlal Mosque to transform into a mecca of moderate Islam in the future, therefore it is necessary to recognize the importance of understanding the digital world so that it is increasingly known globally as an icon of religious tourism, millennials must love the Istiqlal Mosque, so activities at the Istiqlal Mosque must be more productive